Methodical aspects of usage of blended learning in studying the course «Methodology and Distance Learning Technologies» in institute of higher education - O. O. Gnedkova (Academy of Cognitive and Natural Sciences, 2014)
The aim of this study is to examine the practical possibility of use of blended learning technologies in the learning process on the example of course «Methodology and Distance Learning Technologies» in institute of higher education. Objectives of the study is to prove theoretically the concept «blended learning» and to consider methodological features of practical use of blended learning in the learning process in learning the course «Methodology and Distance Learning Technologies». The object of research is the studying the course «Methodology and Distance Learning Technologies» using the blended learning. The subject of research is the methodical aspects of blended learning usage in studying the course «Methodology and Distance Learning Technologies» in institute of higher education. In this work the defined that practical application of blended learning in the educational process have an influence on the improvement of students' knowledge quality, indicating of effectiveness and availability of blended learning usage.